Mitochondrial Permeability Transition and Cell Death: The Role of Cyclophilin D - Javadov, Sabzali; Kuznetsov, Andrey (Frontiers in Physiology, 2013)
Mitochondria serve as a “powerhouse” which provides near 90% of ATP necessary for cell life. However, recent studies provide strong evidence that mitochondria also play a central role in cell death. Irreversible mitochondrial permeability transition (mPT) at high conductance in response to oxidative or other cellular stresses is accompanied by formation of pathological and non-specific mPT pores (mPTP) in the inner membrane of mitochondria. Mitochondrial PTP can serve as a target to prevent cell death under pathological conditions such as cardiac and brain ischemia/reperfusion injury and diabetes. On the other hand, mPTP can be used as an executioner to specifically induce cell death thus blocking tumorigenesis in cancer diseases. Despite many studies, the molecular identity of the mPTP remains unclear. At present, cyclophilin D (CyP-D) represents the only mPTP protein which plays an essential role in pore formation. This review will discuss direct and indirect mechanisms underlying CyP-D interaction with a target protein of the mPTP complex. Understanding of the mechanisms of mPTP formation will be helpful to further develop new pharmacological agents targeting mitochondria-mediated cell death.